3D Foam Anode and Hydrogel Electrolyte for High‐Performance and Stable Flexible Zinc–Air Battery. Issue 27 (20th July 2020) - Qu, Shengxiang; Liu, Bin; Fan, Xiayue; Liu, Xiaorui; Liu, Jie; Ding, Jia; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Zhong, Cheng
Abstract: The development of flexible zinc–air battery (ZAB) is highly desirable in achieving superior and stable electrochemical/mechanical properties. Herein, we developed a Zn‐coated foam anode with three‐dimensional (3D) architecture, obtained by electroplating Zn on Cu foam substrate. The compact outer surface and sufficient amount of metallic Zn could be controlled accurately by selecting appropriate porous substrate and electroplating time on Cu foam. Moreover, adding tetraethylammonium hydroxide (TEAOH) to conventional polyvinyl alcohol (PVA)–KOH hydrogel electrolyte effectively improved the water retention of the semi‐solid electrolyte with stable ionic conductivity. The electrolyte precursor fluid was poured on the uneven outer surface of Zn‐coated foam anode and then frozen crosslinked to increase contact between the 3D anode and the electrolyte. A flexible semi‐solid‐state ZAB based on the 3D Zn‐coated foam anode and the hydrogel electrolyte was assembled and exhibited good discharge performance, high energy density (586.5 Wh kgZn −1 ) and long cycling life. Benefiting from the flexibility of all components, the resultant ZAB performed stable charge and discharge under bending conditions, indicating its promising potential application for flexible and portable energy storage devices. Abstract : The Zn‐coated foam anode has unique 3D architecture and high specific area. The good water retention of the polyvinyl alcohol–tetraethylammonium hydroxide–potassium hydroxide (PVA–TEAOH–KOH) hydrogel electrolyte improves the cycling lifetime of battery. The assembled zinc–air battery exhibits excellent flexibility and stable battery performance.